Electronic and magnetic performance of MoS2 monolayer via Tc & Nb impurities defect and water adsorption - Neupane, Hari; Khatri, Prakash; Devkota, Arun; Adhikari, Narayan Prasad (BIBECHANA, 2023)
This study examined the effect of Tc & Nb impurity atoms on MoS2 (Tc-MoS2 & Nb-MoS2 ), and adsorption of water molecule on impurities defected MoS2 (Tc-W-MoS2 & Nb-W-MoS2) material from first-principles calculations. By the estimation of their ground state energy and binding energy, they are stable 2D materials. From band structure and density of states (DoS) calculations, Tc & Nb impurities affect the nature of pristine MoS2. It is found that Tc-MoS2 has n-type & Nb-MoS2 has p-type semiconducting nature. Water interaction on Tc-MoS2 & Nb-MoS2 slightly changes the electronic properties and impacts the bandgap, which enhanced the electronic performance of material than that of pristine MoS2. The magnetic properties of Tc-MoS2, Nb-MoS2, Tc-W-MoS2, and Nb-W-MoS2 are analyzed and found to exhibit an uneven distribution of up-spin and down-spin states of electrons in the orbital of atoms near the Fermi level. It reflects that they have magnetic properties. The non-magnetic MoS2 material changes in to weak magnetic defected-MoS2 materials due to the presence of Tc, Nb and adsorbed water molecule. It means, impurity defects add to magnetic properties of pristine MoS2. Magnetic properties on defected MoS2 occurred due to the dominant contributions of spin states of 4d-orbital of Mo, Tc, Nb atoms, and 3p-orbital of S atoms in the structures. This study highlights the impact of Tc & Nb impurity atoms and adsorbed water molecule on impurities defected MoS2. The studied materials have potential applications in the fields of catalysis, nanoelectronics, biomedicine, and magnetic sensors on the basis of their electronic and magnetic properties.